2019
DOI: 10.3724/sp.j.1006.2020.91046
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of sowing pattern and planting density on grain yield and nitrogen use efficiency in large spike wheat cultivar

Abstract: In order to find out the way to achieve further improvement in the grain yield (GY) and nitrogen use efficiency (NUE) of winter wheat, two sowing pattern (the wide range sowing and conventional drilling sowing) and seven planting densities (130×10 4 , 200×10 4 , 270×10 4 , 340×10 4 , 410×10 4 , 480×10 4 , and 550×10 4 plants hm-2) were designed during 2015-2016 and 2016-2017 growing seasons. Tainong 18, a winter wheat cultivar with larger spike and lower tillering capacity, was used to investigate the combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…D2 had the highest WUE and WSE under the W2 irrigation volume, while D3 had the highest WUE and WSE under the W3 irrigation volume. These findings are consistent with those of Zhang et al [ 49 ], who demonstrated that an increase in the planting density causes the water use efficiency to increase initially before decreasing.…”
Section: Discussionsupporting
confidence: 93%
“…D2 had the highest WUE and WSE under the W2 irrigation volume, while D3 had the highest WUE and WSE under the W3 irrigation volume. These findings are consistent with those of Zhang et al [ 49 ], who demonstrated that an increase in the planting density causes the water use efficiency to increase initially before decreasing.…”
Section: Discussionsupporting
confidence: 93%
“…However, when the seed rate reached 600 and 700 m −2 , the increase in the yield was decreased. High yields were obtained at SR300 and SR400 under NDS, but the high yields under WBS were obtained at relatively greater seed rates of 400-500 m −2 , and similar results were reported by Zheng et al (2020) [6]. These results suggest that relatively higher seed rates are suitable for enhancing the positive effect of WBS to maximize yields.…”
Section: Discussionsupporting
confidence: 87%
“…PAR intensity above canopy − PAR intensity slightly above the soil surface PAR intensity above canopy × 100 (6) At the anthesis stage in all seasons, we also measured the PAR intensity within the canopy at 0 (slightly above the soil surface), 15, 30, 45, and 60 cm above the soil surface. The relative PAR intensity at a specific canopy height was calculated as follows.…”
Section: Pari (%) =mentioning
confidence: 99%
See 2 more Smart Citations